Analysis of the Mental Health Status and Influencing Factors of Community Health Service Personnel under the Normalization of Epidemic Prevention and Control - Li, Jianhui; Zhou, Zhiwei; Lian, Siyu (International Journal of Social Sciences and Public Administration, 2025)
Objective To understand the mental health status and influencing factors of community health service personnel under the normalization of epidemic prevention and control, and to provide reference for the formulation of psychological intervention programs in the later stage. Methods 200 community health service workers in Guangdong Province were selected by convenient sampling method, and the general situation questionnaire and symptom self-assessment scale (SCL-90) were used. Results The total score of SCL-90 was 112.39 ± 33.31; univariate analysis showed that the position was statistically significant for SCL-90 scores (P